SALES INFORMATION SYSTEM USING THE WEBSITE-BASED RECOMMENDATION FEATURE TO IMPROVE PRODUCT SALES AT SANJAYA STORE - Setyawati, Endang; Paath, David Kristian; Dewi, Fortuna (International Journal of Business and Information Technology, 2021)
The Sanjaya shop is a shop that sells various kinds of machines such as pumps, diesel and many more. Sales of their products are still carried out offline, recording of stock items and prices of goods are still manually recorded in a special book by the owner so that it consumes a lot of paper and also space. The development of information systems is very rapid, many have used information systems to help ease work. This research was created to assist the store in inputting goods, monitoring inventory, sales reports. In addition, the system created has a recommendation feature for buyers based on the best-selling items. This study uses the prototype model as a method for system development. In making the system the author uses PHP and HTML and MySQL as a database. The results of this study can be concluded that the average before using the system is 31.7437 minutes, while the average after using the system is 11.0627 minutes and testing the benefits obtained with excellent results, namely usability of 95.5%, learnability of 97, 7% and the efficiency is 98.9%. From the results that have been obtained, it can be concluded that the Sales Information System Using Website-Based Recommendation Features to Increase Product Sales at Sanjaya Stores can be used properly. With this system, it is expected to be able to assist in the efficiency and effectiveness of recording the stock of goods and sales at the Sanjaya Store.